PSMA PET/CT: joint EANM procedure guideline/SNMMI procedure standard for prostate cancer imaging 2.0 - Fendler, Wolfgang P.; Eiber, Matthias; Beheshti, Mohsen; Bomanji, Jamshed; Calais, Jeremie; Ceci, Francesco; Cho, Steve Y.; Fanti, Stefano; Giesel, Frederik L.; Goffin, Karolien; Haberkorn, Uwe; Jacene, Heather; et al. (European journal of nuclear medicine and molecular imaging, 2023)
Here we aim to provide updated guidance and standards for the indication, acquisition, and interpretation of PSMA PET/CT for prostate cancer imaging. Procedures and characteristics are reported for a variety of available PSMA small radioligands. Different scenarios for the clinical use of PSMA-ligand PET/CT are discussed. This document provides clinicians and technicians with the best available evidence, to support the implementation of PSMA PET/CT imaging in research and routine practice.